FILSAFAT ILMU (FILSAFAT PENGETAHUAN) - Al Ghifari, Barkah; Mortalisa, Tara Putri; Syarnubi; Ibrahim, Duski (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Technological developments facilitate access to information, but create a dependency that often neglects in-depth analysis of the veracity of information. The ability to analyze information is important to maintain the integrity and credibility of information. This research aims to explore the relationship between philosophy and knowledge as two interrelated scientific domains, in order to understand the role of philosophy in shaping the basics of critical thinking and proper knowledge management. Data were taken from relevant books, journals, and articles, analyzed systematically to find the relationship between philosophy and knowledge. The results showed that philosophy, as the “mother of science,” provides a framework for critical and reflective thinking that underlies the process of knowledge development. Knowledge is generated through the interaction between experience, observation, and rational thought. The research also discusses different types of knowledge based on their patterns and levels, including ordinary, scientific, philosophical, and religious knowledge. Philosophy and knowledge complement each other. Philosophy is a tool to understand the nature of truth, while knowledge is the concrete result of the philosophical process. The combination of the two forms a solid foundation for the analysis of information and the development of science, which ultimately helps humans make wise and responsible decisions amidst the challenges of the times.